MENGGALI PENERAPAN KEWIRAUSAHAAN DI PONDOK PESANTREN - Luluk Indarti (LP2M IAIN Sultan Amai Gorontalo, 2021)
Abstract The purpose of this study is to explore entrepreneurship spiritual education in Islamic boarding schools, as well as to support Islamic and religious spiritual education in entrepreneurship education. This research is a qualitative form by using a case study approach in exploring the entrepreneurial process through education in Islamic boarding schools. In this study, data collection using in-depth interview techniques with kyai and supervisors of Islamic boarding schools, observation and document studies. The results show that entrepreneurship is internalized in Islamic boarding schools through religious values ​​and entrepreneurship based on Ibadah (worship of God) and Khidmah (devotion to mankind), where all business and economic activities carried out are aimed at worshiping Allah SWT and for the benefit of the community.